Collaborative opportunistic routing in wireless sensor networks - HU Hai-feng; YANG Zhen (Tongxin xuebao)
The novel protocol of collaborative opportunistic routing was introduced. Based on the region-based routing, rendezvous scheme and sleep discipline, the protocal allowed for routing solution to be improved by cross layer design for wireless sensor networks. The routing objective was to provide robustness to the random variations in network con-nectivity while ensuring better data forwarding efficiency in an energy efficient manner. Finally, Simulation results show that collaborative opportunistic routing performs better than non-collaborative opportunistic routing from perspectives of forwarding efficiency with variable node density.